Prospective observational study of nutritional status and oral supplement utilization in users of an elderly daycare service, employing a web-based Mini Nutritional Assessment Form (MNA plus) - Takano, Hiroki; Kamada, Yukikazu; Ichikawa, Masaki; Yoshida, Sadao (Frontiers in Nutrition, 2024)
Introduction: Seniors are vulnerable to frailty, a condition linked to falls, fractures, hospitalizations, and sarcopenia. Even with regular meals, senior daycare users are at risk for malnutrition. This study assessed malnutrition risk in daycare users, using the web-based Mini Nutritional Assessment Form (MNA®-SF). Individuals identified as malnourished or at risk were examined for changes in nutritional status with and without oral nutritional supplementation (ONS). Results: Of 507 subjects, 138 (27.2%) were malnourished or at risk. Discontinuation rates were 20.0% (7/35) for the ONS group and 40.0% (10/25) for the regular care (RC) group. Among 29 patients with measurable weight change after six months, 19 (ONS group) and 10 (RC group) participated. The ONS group exhibited significant increases in body weight (+1.4±2.9 kg, p <0.01), body mass index (BMI) (+0.6±0.9 kg/m 2, p <0.01), calf circumference (+3.2±0.2 cm, p <0.01), and grip strength (+1.2±1.9 kg, p=0.069). Conversely, the RC group showed no significant increases in body weight (+1.0±1.9 kg, p=0.146), BMI (+0.4±0.8 kg/m 2, p=0.176), or grip strength (-0.7±1.7 kg, p=0.327), with decreased grip strength and calf circumference (-0.8±0.9 cm, p <0.05). In the ONS group, 52.6% (10/19) consumed over 400 kcal/day of ONS, and 84.2% maintained this intake for three months. Malnutrition is prevalent among daycare users. ONS influences weight, BMI, and calf circumference, potentially reducing discontinuation rates. Clinical trial registration: https://center6.umin.ac.jp/cgi-openbin/ctr_e/ctr_view.cgi?recptno=R000049767, UMIN000043580